A One-Dimensional Compound [HgCl2(2,2’-bipy)]n (bipy = bipyridine): Synthesis and Crystal Structure - Chen, Hua-Long; Chen, Wen-Tong; Luo, Qiu-Yan; Xu, Ya-Ping (Asian Journal of Chemistry, 2015)
A mercury chloride bipyridine compound [HgCl2(2,2'-bipy)]n (1) (bipy = bipyridine) has been synthesized through hydrothermal reaction and structurally characterized by single-crystal X-ray diffraction. The title compound features a one-dimensional (1-D) infinite chain-like structure with the mercury ion showing a slightly distorted octahedral geometry. The 1-D chains pile up together through van der Waals interaction to complete three-dimensional (3-D) packing motif.